Developing Adaptive Cruise Control Based on Fuzzy Logic Using Hardware Simulation - Noor Cholis Basjaruddin; Kuspriyanto Kuspriyanto; Didin Saefudin; Ilham Khrisna Nugraha (Institute of Advanced Engineering and Science, 2014)
Ride comfort on the highway often interrupted because drivers need to adjust the vehicle speed. Safe distance between vehicles should be maintained is the main reason. The situation of monotonous and high speed will increase the risk of accidents on highway. A device is required by the driver to adjust the vehicle speed during the long distance (cruise) driving on highway without neglecting the safety aspects. The device is known as Adaptive Cruise Control (ACC). The ACC is a subsystem of Advanced Driver Assistance Systems (ADASs) that serves to assist the driver during cruise driving. The working principle of the ACC is the vehicle speed set automatically so that the distance to the vehicle in front remains safe. This paper presents the development of fuzzy logic controller for ACC. The fuzzy inference method used in this study is Mamdani. The result from hardware simulation that using remote control car shows that the fuzzy logic controller can work according to the design.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6734